Ascaridoid nematode larvae in wild gilthead seabream (Sparus aurata) and European seabass (Dicentrarchus labrax) caught in the Tyrrhenian Sea (Western Mediterranean Sea): a contribute towards the parasitological risk assessment on two commercially important fish species. (December 2020) - Guardone, L.; Susini, F.; Castiglione, D.; Ricci, E.; Corradini, C.; Guidi, A.; Armani, A.
Abstract: Gilthead seabream ( Sparus aurata ) and European seabass ( Dicentrarchus labrax ) are among the most popular fish on the Italian and European market. The present study aimed to assess the occurrence and localization of ascaridoid nematodes in wild specimens of these two species caught in a previously not investigated area of the Tyrrhenian Sea (FAO subarea 37.1.3). Forty gilthead seabream and forty-seven European seabass were analysed through visual inspection and chloro-peptic digestion. All the parasites collected were submitted to morphological and molecular analysis, targeting a fragment of the cytochrome oxidase subunit 2 ( cox2 ) and of the internal transcribed spacer (ITS) genes. No Anisakis spp. were found. As regards other ascaridoid nematodes, seven larvae of Contracaecum rudolphii A (2 in the belly flaps and the rest in the viscera) (Prevalence - P: 2.5 95% Confidence Interval - CI: 0–7.3%; Mean Abundance - MA: 0.017; Mean Intensity - MI: 7) and one visceral larva of Hysterothylacium sp. (P: 2.5 95% CI: 0–7.3%; MA: 0.025; MI: 1) were found in two different specimens of S. aurata . Seventeen larvae of C. rudolphii A were found in the viscera of six D. labrax (P: 12.7% 95% CI: 3.3–22.3%; MA: 0.15; MI: 1.17). The absence of Anisakis sp. in S. aurata agrees with literature data, while variable prevalence values had been previously reported for D. labrax, generally higher in Atlantic grounds. The occurrence of C. rudolphii A and Hysterothylacium spp., nematodes of low or negligible zoonotic impact, respectively, contributes to the characterization of ascaridoid epidemiology in these commercially relevant species. In addition, the presence of the species C. rudolphii A in S. aurata is reported for the first time. The present results contribute towards the parasitological risk assessment of this Italian maritime area, which is also highly dedicated to the aquaculture of S. aurata and D. labrax . Highlights: Occurrence of anisakid nematodes were assess in wild gilthead seabream and European seabass. Fish were sampled in an area of the Tyrrhenian Sea dedicated to fish farming. No Anisakis spp. were found, suggesting a low risk of anisakiasis. Other ascaridoid larvae with a lower or negligible zoonotic impact were found. Data on wild specimens may be useful to feed the parasitological risk for aquaculture.